2008
DOI: 10.1590/s1806-83242008000300004
|View full text |Cite
|
Sign up to set email alerts
|

Coronal and apical leakage analysis of two different root canal obturation systems

Abstract: This study compared the coronal and apical leakage of AH Plus with gutta-percha to that of Epiphany with Resilon. Twenty-four single rooted teeth were instrumented and divided into 2 groups according to the solutions for smear layer removal and the obturation materials employed: Group A -17% EDTA-T and AH Plus with gutta-percha; Group B -primer and Epiphany with Resilon. The Group B specimens were light-cured in the coronal area for 20 s. The external root surfaces were covered with a double layer of ethyl cya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 22 publications
0
17
0
6
Order By: Relevance
“…26 Resilon demonstrated greater ability to fill lateral canals than the other materials evaluated, especially in the apical third of the root. Oddoni et al 27 showed that Epiphany with Resilon provides better apical than coronal sealing. In the coronal third, Resilon had better results than Dentsply gutta-percha, but showed a filling ability similar to Odous gutta-percha.…”
Section: Discussionmentioning
confidence: 99%
“…26 Resilon demonstrated greater ability to fill lateral canals than the other materials evaluated, especially in the apical third of the root. Oddoni et al 27 showed that Epiphany with Resilon provides better apical than coronal sealing. In the coronal third, Resilon had better results than Dentsply gutta-percha, but showed a filling ability similar to Odous gutta-percha.…”
Section: Discussionmentioning
confidence: 99%
“…23 However, Hammad et al 24 analyzed fillings for the presence of gaps and voids in canals obturated with gutta-percha, Resilon, Endorez, or Guta-flow by lateral condensation. The gutta-percha presented the best results, while the canals obturated with Resilon presented greater indices of voids and gaps.…”
Section: Discussionmentioning
confidence: 99%
“…9 The control group was filled using the lateral condensation technique. All simulated root canals of the experimental groups were filled employing the McSpadden technique, varying the type of gutta-percha and time of compaction.…”
Section: Methodsmentioning
confidence: 99%